Microbial growth observation and oil displacement characteristics based on in-situ observation technology of reservoir pore structure - Xu, Wei; Wang, Zhaoyun; Sun, Gangzheng; Song, Xin; Chen, Qiongyao; Li, Caifeng; Wang, Sen; Hu, Yingxue (Frontiers in Chemistry, 2025)
The metabolic products of functional microbial communities used in microbial oil recovery can reduce crude oil viscosity, alter interfacial tension, and modify rock wettability, all of which significantly improve the recovery of residual oil. Therefore, it is crucial to study the mechanisms occurring at the microbe–oil–rock mineral interface in porous media. However, traditional observation techniques struggle to achieve in-situ monitoring, limiting progress in understanding these mechanisms. This study utilized visual microfluidic chip technology to simulate realistic reservoir pore structures and combined it with microscopic in-situ observation techniques to investigate the growth characteristics, diffusion patterns, and oil displacement behavior of bacteria (strain WJ-8) at the pore scale. The results showed that bacterial growth followed the Logistic model, with a rapid growth phase occurring between days 1 and 3, after which the bacteria entered a stable phase and began secreting large amounts of biosurfactants. In the arched chip structure, growth was slower at the ends and faster in the middle. In-situ observations revealed that at the blind ends and edges of pore throats, low flow rates and multiple attachment sites favored bacterial aggregation, enhancing biofilm stability and crude oil detachment. Conversely, within the main pore channels, high shear forces caused dispersed bacterial growth and resulted in lower oil displacement efficiency. By monitoring bacterial activation times at varying distances, the bacterial suspension’s diffusion coefficient was determined to be 1.0 × 10-8–3.0 × 10−8 m2/s, which is higher than that of surfactants. Based on these findings, the optimal shut-in period was suggested to be 30 days. Microbial flooding experiments using the visual reservoir chip indicated that after 30 days of cultivation, the secondary water flooding recovery rate increased by 21.2% (from 28.4% to 49.6%). Emulsification and viscosity reduction by bacterial products, as well as the plugging of high-permeability channels by bacterial clusters, were likely key factors contributing to the improved recovery. This study quantitatively investigates bacterial growth dynamics at the pore scale using in situ observation techniques. The findings provide a theoretical foundation for microbial oil recovery and are significant for advancing its large-scale application.